Active Sensing Based Bolted Structure Health Monitoring Using Piezoceramic Transducers. (18th November 2013) - Wang, R. L.; Gu, H.; Song, G.
Bolted structures are commonly used in civil infrastructure. It is important to perform bolt inspection regularly to ensure the safety of structures. Traditional bolt inspection methods are time-consuming; moreover, bulky instruments are needed in these methods. In this paper, a piezoceramic based active sensing approach is developed to perform the health monitoring of bolted structures. Surface-bonded piezoceramic patches are used as health monitoring transducers. Wavelet packet analysis is used to analyze the sensor data to extract the features that indicate bolt looseness. Based on wavelet packet analysis results, a damage index is developed to quantitatively evaluate the damage status. To verify the effectiveness of the proposed method, a bolted connection experiment with piezoceramic transducers was performed. In the experiment, the looseness of the bolt is adjusted by a torque wrench. Experimental results show that the proposed approach is effective to detect and evaluate bolt looseness.